Pulling together: comprehensive volumes on animal power - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
'Animal-Drawn Wheeled Toolcarriers: Perfected yet Rejected. A cautionary tale of developmenr', Paul Starkey 1988, 161pp, ISBN 3 528 01034 2